MoreMilkIT - Monitoring Survey in Tanzania - Omore, Amos; Rao, E.J.O; Twine, Edgar; Githinji, Julius; Baltenweck, Isabelle; Kariuki, Eunice (International Livestock Research Institute, 2016)
More milk by and for the poor: Adapting dairy market hubs for pro-poor smallholder value chains in Tanzania (MoreMilkIT)